Avaliação in vitro da indução de autofagia e senescência em células de câncer de cólon humano (HCT-116) após tratamento com a quinoxalina PJOV56. - Oliveira, Augusto César Aragão (2018)
Once the current cancer chemotherapy presents inconveniences such as invasiveness, side effects and non-responsiveness the continuous search for new antitumor agents remains as a crucial concern. In order to investigate the action mode of a previously reported cytotoxic quinoxaline derivative, PJOV56, this work aimed to elucidate the cellular senescence and autophagy occurence PJOV56-induced on colon cancer cells, HCT-116. The recovery analysis after PJOV56 3.0 μM treatment withdrawal resulted in persistent antiproliferative effect, showed by Trypan Blue and Real-time proliferation monitoring (XCELLigence) results, while the MTT and cell counting by flow cytometry results indicated recovered cell growth. The compound also promoted changes in cell cycle distribution causing cell accumulation in the S and G0/G1 phases at concentrations of 3.0 and 6.0 μM, respectively. Optical microscopy analysis revealed that the treatment caused increased cell volume and extensive cytoplasmic vacuolization, both common peculiarities to autophagic and senescent phenotypes. Moreover, acridine orange staining assessed by confocal microscopy was elevated, thus indicating autophagy activaction. Additionally the cells showed augmented expression of SA-β-galactosidasis and increased expression levels of LAMA5 and THBS1 genes even after 144 hours of treatment removal, strongly supportting the evidence of senescence after initial contact with the compound. Western Blot analysis indicated a slight increase of Beclin-1 and a gradual elevation in LC3-II levels in a dose-dependent manner, suggesting autophagy. Thus, cellular senescence PJOV56-induced possibly act as the main antiproliferative mechanism of the molecule, at the concentrations and times tested on HCT-116 cells. It is likely that autophagy may act as an effector mechanism of clearance of cancer senescent cells, and may be considered as a new potential anticancer prototype.